2010
DOI: 10.1258/phleb.2009.008072
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the onset and healing rates of venous leg ulcers

Abstract: Venous ulcers exhibit circannual fluctuations in their onset and healing rates. Hypothetically, in addition to exacerbation of chronic venous insufficiency, seasonal variations in immune system activity might potentially be responsible for this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…These results are concordant with previous reports which have indicated seasonal differences in the onset of chronic venous leg ulcers 4,5 . For example, Heede et al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are concordant with previous reports which have indicated seasonal differences in the onset of chronic venous leg ulcers 4,5 . For example, Heede et al.…”
Section: Discussionsupporting
confidence: 93%
“…It is thought that venous reflux penetrates into the venules of the skin, leading to chronic venous ambulatory hypertension which subsequently may result in the onset of leg ulcerations 6 . Because CVI is typically exacerbated at higher temperatures, a peak in the frequency of chronic venous leg ulcers might be expected during the warmer summer months 5 . In our own clinical experiences, ulcer onset, in our patients with chronic leg ulcers, did not appear to correlate with higher temperatures.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…These breakthrough findings have suggested that the thus far unidentified causative pathogen may be a windborne microbe. Other groups have sought to confirm anecdotal findings of seasonal or climate related changes in disease rates, including heart failure [5], depression and anxiety [6], varicose vein ulcers [7], urinary tract infection [8,9], and even cancer [10]. While some of these works searched for seasonality using purpose-driven surveys, Upshur [11] used coded administrative data derived from a large EHR system to investigate whether seasonal peaks in incidence were a common feature in a limited set of the most frequent diagnoses.…”
Section: Introductionmentioning
confidence: 99%